EXPERIENTIAL VALUE ON HALAL FASHION AND EXPERIENTIAL SATISFACTION ON BEHAVIORAL INTENTION - Novi Sekar Sari; Ririn Tri Ratnasari (Universitas Airlangga, 2021)
ABSTRAKIndonesia memiliki peluang besar menjadi barometer halal fesyen dunia. Cara yang harus dilakukan supaya bertahan di industri halal fesyen dengan mempunyai kreativitas dan menghasilkan produk baru yang inovatif. Nilai pengalaman merupakan faktor penting yang memengaruhi keberhasilan, inovasi dan daya saing. Nilai pengalaman dianggap memiliki pengaruh terhadap kepuasan pengalaman dan niat berperilaku. Penelitian ini bertujuan untuk mengidentifikasi dan mengkaji pengaruh nilai pengalaman pada halal fesyen, kepuasan pengalaman dan niat berperilaku dengan objek penelitian Laksmi Muslimah. Penelitian ini menggunakan metode kuantitatif dengan menggunakan path analysis. Penelitian ini memiliki hasil bahwa nilai pengalaman pada halal fesyen berpengaruh terhadap kepuasan pengalaman, kepuasan pengalaman berpengaruh terhadap niat berperilaku, nilai pengalaman pada halal fesyen berpengaruh terhadap niat berperilaku. Penelitian ini memiliki implikasi pada ilmu pemasaran Islam, yaitu pemahaman tentang pengalaman konsumen yang kemudian akan memberikan dampak pada perilaku masa depan seperti merekomendasikan produk/layanan kepada orang lain.Kata Kunci: nilai pengalaman, halal fesyen, kepuasan pengalaman, niat berperilaku. ABSTRACTIndonesia has a great opportunity to become a barometer of the world's halal fashion. The way that must be done to survive in the halal fashion industry is by having creativity and producing innovative new products. Experiential value is an important factor affecting success, innovation and competitiveness. Experiential value is considered to have an influence on experiential satisfaction and behavioral intention. This study aims to identify and examine the effect between the experiential value on halal fashion, experiential satisfaction and behavioral intention with the object of research of Laksmi Muslimah. This study uses quantitative methods using path analysis. This study has the results that the experiential value on halal fashion has an effect on experiential satisfaction, experiential satisfaction has an effect on behavioral intention, the experiential value on halal fashion has an effect on behavioral intention. This research has implications for Islamic marketing science, namely an understanding of consumer experiences which will then have an impact on future behavior such as products/services to others.Keywords: experiential value, halal fashion, experiential satisfaction, behavioral intention. DAFTAR PUSTAKAAli, F., Kim, W. G., Li, J., & Jeon, H.M. (2018). Make it delightful: Customers’ experience, satisfaction and loyalty in Malaysian theme parks. Journal of Destination Marketing & Management, 7(March 2018), 1-11. https://doi.org/10.1016/j.jdmm.2016.05.003Ajzen, I., & Driver, B. L. (1992). Application of the theory of planned behavior to leisure choice. Journal of Leisure Research, 24(3), 207–224. https://doi.org/10.1080/00222216.1992.11969889Anderson, E. W., & Sullivan, M. (1993). The antecedents and consequences of customer satisfaction for firms. Marketing Science, 12(2), 125-143.Bitner, M. J. (1990). Evaluating service encounters: The effects of physical surroundings and employee responses. Journal of Marketing, 54(2), 69-82.Boulding, W., Kalra, A., Staelin, R., & Zeithaml, V. A. (1993). A dynamic process model of service quality: From expectations to behavioral intentions. Journal of Marketing Research, 30(1), 7-28. https://doi.org/10.1177%2F002224379303000102Chang, H. H., Wang, Y. H., & Yang, W. Y. (2009). The impact of e-service quality, satisfaction, and loyalty on e-marketing: Moderating effect of perceived value. Total Quality Management and Business Excellence, 20(4), 423-443. https://doi.org/10.1080/14783360902781923Chen, C. F., & Chen, F. S. (2010). Experience quality, perceived value, satisfaction and behavioral intentions for heritage tourists. Tourism Management, 31(1), 29-35. https://doi.org/10.1016/j.tourman.2009.02.008Cronin, J. J., Brady, M. K., & Hult, G. T. M. (2000). Assessing the effects of quality, value, and customer satisfaction on consumer behavioral intentions in service environments. Journal of Retailing, 76(2): 193–218. https://doi.org/10.1016/S0022-4359(00)00028-2Eid, R., & El-Gohary, H. (2015). The role of Islamic religiosity on the relationship between perceived value and tourist satisfaction. Tourism Management, 46(February 2015), 477-488. https://doi.org/10.1016/j.tourman.2014.08.003Dodds, W. B., & Monroe, K. B. (1991). The effect of brand and price information on subjective product evaluations. Journal of Marketing Research, 28(3), 307-319.Ellis, G. D., & Rossman, J. R. (2008). Creating value for participants through experience staging: parks, recreation, and tourism in the experience industry. Journal of Park and Recreation Administration, 26(4), 1-20.Fu, Y. K., & Wang, Y. J. (2020). Experiential value influences authentic happiness and behavioural intention: Lessons from Taiwan’s tourism accommodation sector. Tourism Review, 76(1), 289-303. https://doi.org/10.1108/TR-06-2019-0228Ha, J., & Jang, S. S. (2010). Perceived values, satisfaction and behavioral intentions: the role of familiarity in Korean restaurants. International Journal of Hospitality Management, 29(1), 2-13. https://doi.org/10.1016/j.ijhm.2009.03.009Lee, T. H., & Chang, Y. S. (2012). The influence of experiential marketing and activity involvement on the loyalty intentions of wine tourists in Taiwan. Leisure Studies, 31(1), 103-121. https://doi.org/10.1080/02614367.2011.568067Gema. (2018). Industri Kecil Media Informasi & Promosi Industri Kecil Menengah. Jakarta: Kemenperin RI.Grewal, D., Levy, M., & Kumar, V. (2009). Customer experience management in retailing: An organizing framework. Journal of Retailing, 85(1), 1-14. https://doi.org/10.1016/j.jretai.2009.01.001Kementerian Perencanaan Pembangunan Nasional. (2018). Masterplan ekonomi syariah Indonesia 2019-2024. Jakarta: KNKS.Holbrook, M. B. (1999). Consumer value: A framework for analysis and research. London, UK: Routledge.Hosany, S., & Witham, M. (2010). Dimensions of cruiser’s experiences, satisfaction, and intention to recommend. Journal of Travel Research, 49(3), 351-364. https://doi.org/10.1177%2F0047287509346859Jin NP, L. S., & Lee H. (2015). The effect of experience quality on perceived value, satisfaction, image and behavioral intention of water park patrons: New versus repeat visitors. International Journal of Tourism Research, 17(1), 82–95. https://doi.org/10.1002/jtr.1968Joy, A., & Sherry, J. (2003). Speaking of art as embodied imagination: A multisensory approach to understanding aesthetic experience. Journal of Consumer Research, 30(2), 259-282. https://doi.org/10.1086/376802Kao, Y. F., Huang, L. S., & Wu, C. H. (2008). Effects of theatrical elements on experiential quality and loyalty intentions for theme parks. Asia Pacific Journal of Tourism Research, 13(2), 163-174. https://doi.org/10.1080/10941660802048480Keller, K. L., & Kotler, P. (2016). Marketing management. United Kingdom: Pearson.Kementerian Agama Republik Indonesia. (2021). Al-Qur’an dan terjemahannya. Jakarta: Kemenag RI.Keng, C.J., & Ting, H. Y. (2009). The acceptance of blogs: Using a customer experiential value perspective. Internet Research, 19(5), 479-495. https://doi.org/10.1108/10662240910998850Kirillova, K., Lehto, X. Y., & Cai, L. (2017). Existential authenticity and anxiety as outcomes: the tourist in the experience economy, International Journal of Tourism Research, 19(1), 13-26.Namkung, Y., & Jang, S. (2007). Does food quality really matter in restaurant?: its impact on customer satisfaction and behavioral intentions. Journal of Hospitality and Tourism Research, 31(3), 387-410. https://doi.org/10.1177%2F1096348007299924Oliver, R. L. (1997). Satisfaction: A behavioral perspective on the consumer. New York: McGraw-Hill.Othman, Z., Zahari, M. S. M., & Radzi, S. M. (2013). Customer behavioral intention: influence of service delivery failures and service recovery in Malay restaurants. Procedia-Social and Behavioral Sciences, 105(December 2013), 115-121. https://doi.org/10.1016/j.sbspro.2013.11.013Pandza B. I. (2015). Tourist perceived value, relationship to satisfaction and behavioral intentions: the example of the Croatian tourist destination Dubrovnik. Journal of Travel Research, 54, 122-134. https://doi.org/10.1177/0047287513513158Parasuraman, A., Zeithaml, V. A., & Berry, L. L. (1996). The behavioral consequences of service quality. Journal of Marketing, 60(2), 31-46. https://doi.org/10.2307/1251929Pine, J. B., & Gilmore, J. H. (1998). Welcome to the experience economy. Harvard Business Review, 76(4), 97-103.Pine, B. J., & Gilmore, J. H. (2011). The experience economy. Boston: Harvard Business Review Press.Pizam, A., Shapoval, V., & Ellis, T. (2016). Customer satisfaction and its measurement in hospitality enterprises: A revisit and update. International Journal of Contemporary Hospitality Management, 28(1), 2-35. https://doi.org/10.1108/IJCHM-04-2015-0167Ratnasari, R. T., Gunawan, S., Mawardi, I., & Kirana, K. C. (2020). Emotional experience on behavioral intention for halal tourism. Journal of Islamic Marketing, 12(4), 864-881. https://doi.org/10.1108/JIMA-12-2019-0256Reichheld, F. (1996). The loyalty effects: The hidden force behind growth, profit, and lasting value. Boston: Harvard Business School Press.Shah Alam, S. Mohd, & Hashim, R. (2011). Is religiousity an important determinant on Muslim consumer behaviour in Malaysia? Journal of Islamic Marketing, 2(1), 83-96. https://doi.org/10.1108/17590831111115268Stamboulis, Y. & Skayannis, P. (2003). Innovation strategies and technology for experience-based tourism. Tourism Management, 24(1), 35-43. https://doi.org/10.1016/S0261-5177(02)00047-XStandard, D. (2019). State of the Global Islamic Economy Report 2019/20. Dubai International Financial Centre, 1–174. https://haladinar.io/hdn/doc/report2018.pdfStorbacka, K., Strandvik, T., & Grönroos, C. (1994). Managing customer relationships for profit: The dynamics of relationship quality. International Journal of Service Industry Management, 5(5), 21–38. doi:10.1108/09564239410074358Verhagen, T., Feldberg, F., Van den Hooff, B., Meents, S., & Merikivi, J. (2011). Satisfaction with virtual worlds: An integrated model of experiential value. Information and Management, 48(6), 201-207. https://doi.org/10.1016/j.im.2011.02.004Westbrook, R. A., & Oliver, R. L. (1991). The dimensionality of consumption emotion patterns and consumer satisfaction. Journal of Consumer Research, 18(1), 84–91. doi:10.1086/jcr.1991.18.issue-1Wu, C. H. J., & Liang, R. D. (2009). Effect of experiential value on customer satisfaction with service encounters in luxury-hotel restaurants. International Journal of Hospitality Management, 28(4), 586-593. https://doi.org/10.1016/j.ijhm.2009.03.008Wu, C. W. (2015). Foreign tourist’s intentions in visiting leisure farms. Journal of Business Research, 68(4), 757-762. https://doi.org/10.1016/j.jbusres.2014.11.024Wu, H. C., Li, M. Y., & Li, T. (2014b). A study of experiential quality, experiential value, experiential satisfaction, theme park image, and revisit intention. Journal of Hospitality & Tourism Research, 42(1), 26-73. https://doi.org/10.1177%2F1096348014563396Wu, H. C., Cheng, C. C., & Ai, C. H. (2018). A study of experiential quality, experiential value, trust, corporate reputation, experiential satisfaction and behavioral intentions for cruise tourists: The case of Hong Kong. Tourism Management, 66(June 2018), 200–220. https://doi.org/10.1016/j.tourman.2017.12.011Yang, J., Gu, Y., & Cen, J. (2011). Festival tourists’ emotion, perceived value, and behavioral intentions: a test of the moderating effect of festivalscape. Journal of Convention & Event Tourism, 12(1), 25-44. https://doi.org/10.1080/15470148.2010.551292Yoon, S. Y., Lee, J. S., & Lee, C. K. (2010). Measuring festival quality and value affecting visitors’ satisfaction and loyalty using a structural approach. International Journal of Hospitality Management, 29(2), 335-342. https://doi.org/10.1016/j.ijhm.2009.10.002Zeithaml, V. A., Berry, L. L., & Parasuraman, A. (1996). The Behavioral Consequences of Service Quality. Journal of Marketing, 60(2), 31-46. https://doi.org/10.2307/1251929